The non-monotypic status of the neotropical fish genus Hemiodontichthys (Siluriformes, Loricariidae) evidenced by genetic approaches - Carvalho, Margarida Lima; Costa Silva, Guilherme Jose da [UNESP]; Melo, Silvana [UNESP]; Ashikaga, Fernando Yuldi [UNESP]; Shinnabukuro-Dias, Cristiane Kioko [UNESP]; Scacchetti, Priscilla Cardim [UNESP]; Devide, Renato [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Taylor & Francis Ltd, 2018)
The combination of cytogenetic and molecular data with those traditionally obtained in areas like systematics and taxonomy created interesting perspectives for the analysis of natural populations under different aspects. In this context, this study aimed to evaluate the genetic differentiation among populations of the genus Hemiodontichthys Bleeker, 1862, through combined genetic techniques and included the analysis of populations sampled in the Araguaia River, Guama River, Madeira River and two populations from the Purus River. Hemiodontichthys samples from the two localities in Purus River were also karyotyped in order to address the degree of chromosomal variation between populations. Through GMYC analysis of the COI tree, the patterns of genetic variation among local populations revealed to be higher than the ones found among distinct species from other genera of the subfamily Loricariinae, suggesting the existence of probable four cryptic species in this genus. The possible existence of a species complex in the genus is corroborated by the different cytogenetic patterns between Hemiodontichthys sp. 1 and sp. 2, revealing the necessity of a deep taxonomic review of the group.
Keywords: Neotropical fish; DNA barcode; molecular cytogenetics; species complex